The Gothic Tradition in Hovard Lovecraft's Creative Activity - Tuzkov, Sergey (Pitannâ lìteraturoznavstva, 2014)
The main motives of H. Lovecraft’s story “The Call of Cthulhu” are marked out in the article. They give the possibility to examine the writer’s creative activity in the context of the gothic tradition: doom of human civilization, overcoming the limits between modern and ancient worlds, between reality and dreams, perception of human life as mysticism and horror, aspiration to make the reader feel the reality of the fantastic plot. It is noted that these motives not only form the subject-composition structure of the story “The Call of Cthulhu” but at the same time unite H. Lovecraft’s works into the joint cycle. The advantage of this research is that H. Lovecraft’s prose is considered to be the link between E. Poe's novelistics and modern literature of “horror” genre. The thought that humanity is only one of the great variety of highly-advanced civilizations inhabited the Earth at different times becomes the main motive of H. Lovecraft’s works. The idea of projection of the consciousness of the ancient die off civilization representatives into the future is connected with this motive. In H. Lovecraft’s story the idea of the consciousness shift from one body into another is viewed in the context of the eternal subject of the fight of good and evil. In its turn the “dream in dream” motive creates the feeling of the current developments illusiveness with the characters of the story as well as with readers. In the result of the story “The Call of Cthulhu” analysis the conclusion that the atmosphere of fear, supernatural horror, mystery, appealing to infernal forces allows (in half-mystical or half-mythical way) to judge H. Lovecraft’s works as peculiar variations about the gothic themes is made. It is possible to claim with certainty that H. Lovecraft’s creative activity predetermined in many ways the development of the modern neo-gothic prose.